Chiral aryl oxazolines as templates in the enantioselective synthesis of biologically active compounds - Degnan, Andrew P., author; Meyers, A. I., advisor (Colorado State University. Libraries, 2000)
Lithium dialkvlamides underwent a highly enantioselective conjugate addition to chiral naphthvloxazolines to afford, upon electrophilic trapping. 1.1.2-trisubstituted dihydronaphthyloxazolines. This method was used to install the ethylene ketal of 4-piperidone. Hydrolysis of the ketal and a double retro-Michael addition liberated the primary amine The synthetic sequence culminated in the preparation of a novel. N-tosylhexahydrobenz[e]indole Lithium dimethylphenylsilyllithium also underwent the tandem addition reaction to afford the 1.1.2-trisubstituted dihydronaphthyloxazoline as a single diastereomer. The silicon, thus incorporated, was protodesilylated and underwent Tamao oxidation to afford the corresponding alcohol. By chemical modification of the oxazoline, both the γ- and δ-lactones were prepared. Reduction of each lactone followed by oxidation of the ensuing diol gave the keto aldehyde. Double reductive amination of the 1.4-dicarbonyl (from the γ-lactone) allowed the synthesis of two novel hexahydrobenz[e]indoles. Double reductive amination of the 1,5-dicarbonyl (from the δ-lactone) gave access to two novel octahydrobenzo[f]quinolines. A chiral, non-racemic bicyclic lactam was utilized to create a chiral cvclopentane. containing vicinal quaternary carbon centers which is common to (-)-herbertenedioI. (-)- m astigophorene A, and (-)-m astigophorene B. The benzylic methyl group of O.O-dimethylherbertenediol was oxidized to the benzoic acid and condensed with amino alcohols to afford the corresponding oxazoline. An oxazoline-mediated asymmetric Ullmann coupling was then utilized to create the chiral biaryl axis of mastigophorene A and mastigophorene B. Through the course of this synthesis, it was clearly demonstrated that smaller chiral auxiliaries lead to higher levels of atroposelection - a previously unknown phenomenon of the asymmetric Ullmann coupling.
Keywords: organic chemistry